2022
DOI: 10.3390/pharmaceutics14020288
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Rapid and Easy-to-Apply Method to Simultaneously Quantify Co-Loaded Dexamethasone and Melatonin PLGA Microspheres by HPLC-UV: Encapsulation Efficiency and In Vitro Release

Abstract: This paper discusses the development and validation of a rapid method for the reversed phase HPLC-UV quantification of biodegradable poly(D,L-lactic-co-glycolic) acid (PLGA) microspheres co-loaded with two neuroprotective agents (dexamethasone and melatonin) (DX-MEL-MSs) to be intravitreally administered as a promising glaucoma treatment. The study was performed to validate two procedures that quantify the content of the two active substances entrapped into the polymer matrix during an encapsulation efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The free concentration was also determined using the centrifugal filters of 50 kDa (14,000 rpm for 5 min), using a volume of 0.5 mL. As travoprost was not detected in the aqueous dispersion, it was necessary to determine the Y-intercept, slope, and the limit of quantification to determine the minimum encapsulation efficiency [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The free concentration was also determined using the centrifugal filters of 50 kDa (14,000 rpm for 5 min), using a volume of 0.5 mL. As travoprost was not detected in the aqueous dispersion, it was necessary to determine the Y-intercept, slope, and the limit of quantification to determine the minimum encapsulation efficiency [ 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the optimal dosage remains to be confirmed. PLGA microspheres were also used for the delivery of dexamethasone, melatonin, and coenzymeQ10 [ 119 , 120 ]. This multitherapy reduced RGC loss along with reducing retinal stress of multiple single doses and showed good tolerance in their in vivo model.…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…Many studies have been reported on PLA-HA [249] or PLA-polycaprolactone-hydroxyapatite composite materials that have highlighted their promising preliminary results for biomedical applications [250]. As a hydrophilic and highly crystalline polymer, with a relatively fast degradation rate in aqueous solutions or in vivo, PGA can be used in drug delivery [251], biological adhesives/glues [252], oral surgical treatments and injectable microspheres [253].…”
Section: Biodegradable Polymersmentioning
confidence: 99%